Digital Representation of Inuvialuit Traditional Knowledge: A case study in community engagement using Google Earth - Grieve, Jeffrey (Scholarship@Western, 2019)
Many Indigenous communities are mobilizing to document and share their traditional knowledge and cultural heritage. Information technology has created new opportunities for Indigenous communities, archaeologists, heritage groups, and technologists to collaborate on digital strategies to meet these objectives. Every Indigenous community has a unique history and world view, so the use of these digital approaches must be tailored to the needs of each case. The Inuvialuit are the Inuit of the Western Arctic, and their traditional knowledge is practiced through land-based activities such as hunting and fishing. The spatial nature of these activities has good potential to be represented in an interactive Google Earth map in a way that uniquely aligns with Inuvialuit epistemology and worldviews. This paper discusses the effectiveness, benefits, challenges, and implications of using Google Earth for the documentation and intergenerational sharing of Inuvialuit traditional knowledge and cultural heritage